Optimization of olive growing practices in Spain from a life cycle assessment perspective. (15th April 2017) - Romero-Gámez, Mercedes; Castro-Rodríguez, Juan; Suárez-Rey, Elisa M.
Abstract: Recently, the Spanish olive sector has undergone deep changes regarding agronomic practices. Olive grove cultivation tends to move from traditional low-density to new high-density cropping systems. Irrigation has produced a major change in the olive grove sector and the integrated production plays an important role due to the application of rational farming techniques. The aim of this study was to compare the environmental impacts of a high diversity of olive growing systems existing in Spain, including the integrated production systems. The Life Cycle Assessment methodology has been used to calculate and evaluate potential environmental impacts associated to the olives production phase from the extraction of the raw materials to the oil mill gate. Eight traditional systems, three intensive systems and one super-intensive system were selected to be compared. The agricultural practices were grouped in different stages each one including processes and flows: irrigation, soil management, pruning, fertilizers, pesticides and harvesting. Impact categories such as climate change, acidification, freshwater eutrophication, freshwater ecotoxicity, land use and water resource depletion were selected. The fertilizers stage was clearly the highest contributor in all impact categories, specifically, in the climate change and acidification categories in the intensive not irrigated conventional system. Thus, optimization of fertilization should be the first priority to optimize olive growing. The systems that showed the largest environmental impact for most categories were the intensive irrigated integrated system and the super-intensive irrigated integrated system, despite having higher productivity compared to the rest. The organic systems presented the lowest impacts but should improve their productivity. Integrated production was the best olive fruit production system from an overall environmental and productive point of view, especially the traditional mechanized systems. Highlights: This is the first LCA study for the olive oil growing systems in Spain. LCA methodology proved to be a useful tool to evaluate the environment burdens. Optimization of fertilization should be the first priority to optimize olive growing. TMRI and TMII were the systems with minor environmental impact and high productivity.